2006
DOI: 10.1063/1.2260827
|View full text |Cite
|
Sign up to set email alerts
|

Strongly enhanced shot noise in chains of quantum dots

Abstract: We study charge transport through a chain of quantum dots. The dots are fully coherent among each other and weakly coupled to metallic electrodes via the dots at the interface, thus modelling a molecular wire. If the non-local Coulomb interactions dominate over the inter-dot hopping we find strongly enhanced shot noise above the sequential tunneling threshold. The current is not enhanced in the region of enhanced noise, thus rendering the noise super-Poissonian. In contrast to earlier work this is achieved eve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Very recently transport properties of triple quantum dots have become a subject of intensive studies due to various interesting effects that emerge in such structures [32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50]. In particular, triple dots enable the investigation of spin-entangled currents [32], dark states [37,41], or various interference effects [34,39].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently transport properties of triple quantum dots have become a subject of intensive studies due to various interesting effects that emerge in such structures [32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50]. In particular, triple dots enable the investigation of spin-entangled currents [32], dark states [37,41], or various interference effects [34,39].…”
Section: Introductionmentioning
confidence: 99%
“…However, several theoretical works on various systems have showed that Coulomb interactions might also lead to a super-Poisson shot noise with a Fano factor F > 1. Examples of such systems are quantum dots that are coupled to ferromagnetic leads [7][8][9][10] , multi-levels quantum dots 11,12 , multidots structures [13][14][15][16][17][18] , and also three terminal quantum dots [19][20][21] . There are also experimental works [22][23][24][25][26] in which a super-Poisson noise was measured in quantum dots, rather than the sub-Poisson noise, which is expected from the single level model of the quantum dots.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] The noise spectrum measures the temporal correlation between individual electron events. It has been proven to be a powerful tool to reveal different possible mechanisms which are not accessible by the mean current measurement.…”
Section: Introductionmentioning
confidence: 99%